2021
DOI: 10.1038/s41375-021-01288-0
|View full text |Cite
|
Sign up to set email alerts
|

Seroconversion and dynamics of the anti-SARS-CoV-2 antibody response related to a hospital COVID-19 outbreak among pediatric oncology patients

Abstract: Two recent reports published in Leukemia have described the antibody response to SARS-CoV-2 infection in adult patients with chronic lymphocytic leukemia (CLL) [1] and acute leukemia [2] in conjunction with PCR-confirmed COVID-19. These studies have demonstrated that 14/21 (67%) of the examined CLL patients and 7/8 (88%) of the examined acute leukemia patients produced anti-SARS-CoV-2 IgG antibodies. Importantly, 6 out of 7 IgG-positive acute leukemia patients developed virus-neutralizing antibodies [2], assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Similar investigation was published only by the Moscow group. They investigated a larger number of patients in multiple timepoints and found a 100% seroconversion after 6-weeks which started to decrease after three consecutive weeks to 54% by week 18, similar to our findings [ 14 ]. These results indicate that pediatric cancer patients, immunocompromised due to their underlying malignancy and its treatment, are able to mount a humoral immune response against the SARS-CoV-2 infection, however, this natural immunity may decline four to 5 months after harboring the infection leaving patients unprotected against a reinfection in a new wave of epidemics without vaccination.…”
Section: Discussionsupporting
confidence: 91%
“…Similar investigation was published only by the Moscow group. They investigated a larger number of patients in multiple timepoints and found a 100% seroconversion after 6-weeks which started to decrease after three consecutive weeks to 54% by week 18, similar to our findings [ 14 ]. These results indicate that pediatric cancer patients, immunocompromised due to their underlying malignancy and its treatment, are able to mount a humoral immune response against the SARS-CoV-2 infection, however, this natural immunity may decline four to 5 months after harboring the infection leaving patients unprotected against a reinfection in a new wave of epidemics without vaccination.…”
Section: Discussionsupporting
confidence: 91%
“…Another study reported dynamics of the anti-SARS-CoV-2 antibody response; seroconversion was observed in 92% of patients (16 with ALL, and 2 brain tumors) by week 3 and in 100% of patients by week 6 post exposure. The seropositivity rate was maintained at around 80% for at least three consecutive weeks, declining to 54% by week 18 post exposure ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, by 18 weeks after the onset of COVID-19, this seropositivity rate declined to 54%. However, the authors did not compare the level of antibodies with an immunocompetent control group [12]. On the other hand, researchers from Hungary assessed the level of antibodies in 10 children with cancer at an interval of 1 to 4.5 months after the onset of COVID-19.…”
Section: Discussionmentioning
confidence: 99%